Segregation of Foreign Language Epistemology in Boarding Schools in the Context of Communication Ethnography - Wahyu Hanafi Putra; Lisma Meilia Wijayanti (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2022)
This study aims to describe the epistemic segression of foreign languages ??in Islamic boarding schools in the modernization era in the context of communication ethnography. This research uses a qualitative approach with the type of Library Research. The data used in this study were obtained from various scientific literature that reviews foreign language learning in Islamic boarding schools. The data collection technique used by researchers is documentation. The data analysis technique uses content analysis. The results of this study state that the Arabic language taught in traditional Islamic boarding schools has an ethnological message. Santri are able to read the yellow book and understand fiqh, tasawuf, kalam, and tafsir literature. Traditional Islamic boarding schools' cultural traditions also influence the folklore process in forming non-verbal language. Symbols become a semiotic element of conveying non-verbal language messages. Santri can communicate well in foreign languages ??to face globalization, so in this community, language becomes essential in driving Islamic boarding school life. Verbal language folklore will quickly form with activities that require foreign languages ??in every situation. The goals of learning foreign languages ??and folklore in the two pesantren will affect different language constructions. Language is a factor in forming a relatively heterogeneous pesantren speech community. Keywords: Language, Islamic Boarding School, Folklore, Ethnography, Communication